The Effect of Papaya Vinegar (Carica papaya L) Marinating Time on the Physical Quality of Horse Meat (Equus caballus) - Bintang Hugi Prayoga; Nurzainah Ginting; Nurjama’yah Br.Ketaren; Syaheera N Ibrahim (Talenta Publisher, 2026)
Marination is a process used to soak meat, which functions to improve physical quality of meat. Horse meat has a high protein content of around 19.72% with a low fat content of 4.84%. To improve its quality, natural marination are needed, including papaya vinegar. Papaya can be used as a natural marination because it contains protease enzymes, namely papain enzymes. Papain enzymes function as catalysts in protein hydrolysis reactions that can improve meat quality. This research was conducted in January - April 2025 at the Animal Production Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, and the Chemistry Department Testing Laboratory, Lhokseumawe State Polytechnic. The design used in this study was a Completely Randomized Design (CRD) with 4 treatments dan 5 replications. The treatment consisted of giving papaya vinegar as much as 25% in each treatment (P0 = control; P1 = 15 minutes; P2 = 30 minutes; P3 = 45 minutes of marination). The parameters observed were pH value, water holding capacity, cooking loss, and meat tenderness. The results showed that the duration of papaya vinegar marination on the physical quality of horse meat had a significant effect on water holding capacity and tenderness